2020
DOI: 10.1002/bies.202000221
|View full text |Cite
|
Sign up to set email alerts
|

Afadin (AF6) in cancer progression: A multidomain scaffold protein with complex and contradictory roles

Abstract: Adherens (AJ) and tight junctions (TJ) maintain cell-cell adhesions and cellular polarity in normal tissues. Afadin, a multi-domain scaffold protein, is commonly found in both adherens and tight junctions, where it plays both structural and signal-modulating roles. Afadin is a complex modulator of cellular processes implicated in cancer progression, including signal transduction, migration, invasion, and apoptosis. In keeping with the complexities associated with the roles of adherens and tight junctions in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…7 h). Recent research revealed that afadin, an F-actin-binding protein, plays an important role in BC liver metastasis, and a lack of afadin significantly diminished the colony-forming ability of BC cells and metastasis formation in the liver [ 15 , 16 ]. Next, we found that the protein level of afadin was not only correlated with the expression of circROBO1 but also associated with the status of autophagy as assessed by western blot, whereas the mRNA level of afadin remained almost unchanged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7 h). Recent research revealed that afadin, an F-actin-binding protein, plays an important role in BC liver metastasis, and a lack of afadin significantly diminished the colony-forming ability of BC cells and metastasis formation in the liver [ 15 , 16 ]. Next, we found that the protein level of afadin was not only correlated with the expression of circROBO1 but also associated with the status of autophagy as assessed by western blot, whereas the mRNA level of afadin remained almost unchanged (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As for the TJ formation–promoting activity of LPA in an E-cadherin-based cell adhesion–independent manner in E-cadherin -KO and αE-catenin- KO and the AJC organization–promoting activity of LPA in afadin -KO EpH4 cells, these activities may operate in various cancers in which E-cadherin, αE-catenin, or afadin is lost or downregulated ( 59 , 60 , 61 ). In addition, the reduced activities of E-cadherin, αE-catenin, and afadin have been reported: For instance, inactivating mutations of E-cadherin are frequently detected in infiltrating lobular breast carcinomas and in diffuse gastric cancer ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remained elusive how the AJC structure and the apicobasal polarity are impaired in T47D cells stably expressing both nectin-4 and p95-ErbB2. It was noted that these cells were deficient of afadin, and afadin deficiency is observed in many cancer cells, such as colon, breast, pancreatic, osteosarcoma, myometrial cancers, and acute myeloid leukemia (Huxham et al, 2021). It is possible that this afadin deficiency in T47D cells stably expressing both nectin-4 and p95-ErbB2 causes the impaired AJC structure and the apicobasal polarity and multilayered proliferation in an adherent culture.…”
Section: Localizations Of Cell Polarity Molecules In Parental T47d An...mentioning
confidence: 99%